Context-dependent functions of KLF4 in cancers: Could alternative splicing isoforms be the key?. (1st December 2018) - Wang, Liang; Shen, Feng; Stroehlein, John R.; Wei, Daoyan
Abstract: Krüppel-like factor 4 (KLF4) is an important transcription factor that is expressed in a variety of tissues and regulates many critical physiologic and cellular processes, including cell proliferation, differentiation, stem cell reprogramming, maintenance of genomic stability, and normal tissue homeostasis. KLF4 has both tumor suppressive and oncogenic functions in gastrointestinal and other cancers. These functions are thought to be context dependent, but how KLF4 exerts these differential functions and the molecular mechanisms behind them remain poorly understood. Recent studies have shown that the KLF4 gene undergoes alternative splicing, and the protein products of certain transcripts antagonize wild-type KLF4 function, suggesting an additional layer of regulation of KLF4 function. Therefore, detailed study of KLF4 alternative splicing may not only provide new insights into the complexity of KLF4 functions but also lead to rational targeting of KLF4 for cancer prevention and therapy. Highlights: KLF4 regulates variety of cellular processes. Alterations of KLF4 expression and function associate with cancer development and progress. KLF4 has context-dependent functions in different types of cancer. KLF4 gene undergoes alternative splicing. Knowledge of KLF4 alternative splicing may unravel its context-dependent functions.